Tensile and Flexural Properties of Aramid Fiber Composite Laminates - Halim, Muhammad Asyraaf; S Kanna A/L Subramaniyan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Composite laminates are a type of materials that being develop currently as for their lightweight, strength and renewable compared to traditional materials which is steel. These materials are being used widely in automotive and aerospace industry because if their benefits. This study focus on developing strong composite laminates materials from aramid fiber. The objectives of the study are to fabricate the composite laminates of aramid fiber and to evaluate the mechanical properties of the composite laminates which are tensile and flexural strength. The fabrication method used in this research was vacuum assisted infusion molding with infusion of 2:1 epoxy resin to hardener ratio. There are two types of samples with different layer of aramid fiber which are 4 and 6 layers. The composite laminates are then cut using vertical bandsaw machine into desired shape and size required for the testing. The tensile and flexural strength is obtained by testing the material using universal testing machine. Tensile test referred to ASTM D3039 standard and flexural test referred to ASTM D790 standard. The mechanical properties of the composite laminates fabricated using this method tend to be superior to another research which use compression molding and polyester resin. The maximum load of the tensile properties for both 4- and 6-layer composite laminates sample were 6.01 kN and 8.12 kN respectively. The maximum load for the flexural properties of both 4- and 6-layers composite laminates were 156.875 N and 461.458 N respectively.